The Effect of Production Costs and Long-Term Debt on Profitability in The Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange - Umi Kalsum; Nurwani (Journal Research of Economic and Bussiness, 2022)
ABSTRACT The purpose of this research was to examine the influence and analyze of production costs and long-term debt on profitability was 48 hotel, restaurant, and tourism companies listed in the Indonesia Stock Exchange in the period of 2015-2019 and samples of 10 companies by using purposive sampling technique. The data were processed by using multiple linear regression analysis. The result of the research showed that first, production cost had influence positive and significant on profitability. Secondly showed that long-term debt had influence negative and significant on profitability. Thirdly showed that production costs and long-term debt influence significant on profitability simultaneously.